Visitors' Satisfaction of Recreational Trail Conditions in Thingvellir National Park, Iceland - Huber, Charlotte, 1987- (2014)
Nature-based tourism plays an important role for Iceland as a tourist destination. Its unique landscapes and pristine nature attracts visitors from all over the world. Hiking and horse riding are among the most popular tourism activities in Iceland. Such recreational activities in fragile natural areas like Iceland can however cause negative impacts on the environment. This thesis presents a case study carried out in Thingvellir National Park in southwestern Iceland. The overall aim was to determine visitors’ satisfaction level concerning condition of recreational trails within the national park as well as their level of environmental awareness. A questionnaire survey among hikers and riders within the national park was carried out in the summer of 2013. Additionally interviews with managers in the national park as well as riding tour operators were conducted to assess options towards sustainable trail management. Results show that the overall satisfaction level amongst riders and hikers within Thingvellir National Park is very high. The park’s recreational trail network is shared by many different visitors with diverse intentions and needs, no signs of conflicts of interest or other problems between the user groups were noted. As a main dissatisfaction the visitors’ survey identifies insufficient labeling and signposting along the trails. In terms of visual disturbances trail erosion, trampling effects of horses and secondary trails are the three most disturbing issues. Other issues such as leaving the trail or scarcity of sanitary facilities within the trail network are also noted. Knowledge about the environmental code of conduct furthermore seems to be limited. A general demand for more educational material on environmental topics, as well as signs with reminders of environmental code of conduct is emphasized by most interviewees. Potential improvements on the trail system include construction and widening of the trails. Such actions do however ask for careful weighing of needs, because on the one hand is ...